Domesticity in the Making of Modern Science
XII, 299 p.
Keywords: The history of the modern sciences has long overlooked the significance of domesticity as a physical, social, and symbolic force in the shaping of knowledge production. This book provides a welcome reorientation to our understanding of the making of the modern sciences globally by emphasizing the centrality of domesticity in diverse scientific enterprises.